Between remembrance and knowledge: The Spanish Flu, COVID-19, and the two poles of collective memory. (December 2021) - Vinitzky-Seroussi, Vered; Jalfim Maraschin, Mathias
While the literature suggests that the Spanish Flu—despite the devastation it caused—suffers from social amnesia, this article begs to differ. Building on the multiplicity of manners in which the past maintains itself in the present and specifically focusing on Erll's distinction between remembrance and knowledge as two poles of collective memory, we shed light on the collective memory of the Spanish Flu in its entirety. First, our analysis recognizes COVID-19 as a catalyst of the remembrance of the Spanish Flu. Second, it suggests that the perceived social amnesia attached to the Spanish Flu stems from overlooking the mark it left on the sphere of knowledge. The article addresses the need to recognize the uniqueness and importance of the knowledge pole in assessing collective memory, and exposes the dynamics and potential relationships shared by the poles.